Subconjunctival Loa Loa Worm: a First Native Case Report in a Moroccan Child - Lalaoui, Abdessamad; Nassih, Houda; Qadiry, Rabiy El; Mahir, Nahid; Bourahouat, Aicha; Sab, Imane Ait; Berradi, Soufiane; Moutaj, Redouane (Archives of Clinical and Medical Case Reports, 2020)
The loiasis is limited to, Western and Central Africa. Characteristic clinical features include Calabar swellings and subconjunctival migration of the adult parasite. Severe complications of infection, including cardiomyopathy, nephropathy, and fatal encephalitis, are rare, but do occur. So far, all Moroccan cases are seen in adult travelers. We report the first case of autochthone loiasis in a Moroccan child. <gdiv></gdiv>